High-strength high-seawater-corrosion-resistance concrete and preparation method thereof

By using high-strength, high-seawater corrosion-resistant concrete optimized by ferroate cement and mineral blends, the problems of poor durability and inverted strength in marine tidal zone applications are solved, and higher resistance to chloride ion corrosion and durability are achieved.

CN119638341APending Publication Date: 2025-03-18ZHENGZHOU UNIV +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411767555.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing silicate cement and sulfaluminate cement have problems of poor durability and inverted strength in the application of marine tidal zones, especially under seawater erosion and freeze-thaw cycle conditions.

Method used

Ferroaluminate cement (FAC) is used as the main cementitious material, and mineral blends such as fly ash, mineral powder and silica fume are combined to optimize the mix ratio and preparation process of concrete to form a low porosity and dense cement stone structure.

Benefits of technology

It significantly improves the resistance to chloride ion corrosion and durability of concrete, avoids strength retractability, and maintains good mechanical properties under dry and wet cycle conditions of seawater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169376110000071
    Figure BDA0005169376110000071
  • Figure BDA0005169376110000081
    Figure BDA0005169376110000081
  • Figure BDA0005169376110000082
    Figure BDA0005169376110000082
Patent Text Reader

Abstract

The invention discloses high-strength and high-seawater-corrosion-resistance concrete and a preparation method thereof. The high-strength and high-seawater-corrosion-resistance concrete is prepared from 400 parts by mass of a cementing material, 1180-1200 parts by mass of coarse aggregate, 610-640 parts by mass of fine aggregate, 1.1-1.5 parts by mass of a water reducing agent and 175-185 parts by mass of water, wherein the cementing material comprises 310 to 325 parts by mass of iron aluminate cement and 75 to 90 parts by mass of fly ash, or 275 to 285 parts by mass of iron aluminate cement and 115 to 125 parts by mass of mineral powder, or 360 to 380 parts by mass of iron aluminate cement and 20 to 40 parts by mass of silica fume. According to the invention, the problems of poor durability and reduced strength of ordinary Portland cement and sulphoaluminate cement when being applied to ocean tidal zones are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to high-strength and high-seawater corrosion-resistant concrete and a preparation method thereof. Background Art

[0002] With the rapid development of the global marine economy, marine engineering construction is increasing. Traditional Portland cement has poor durability in marine environments due to factors such as chloride ion corrosion, sulfate corrosion, marine biofouling, and freeze-thaw cycles, seriously affecting the service life and safety of projects. Therefore, the development of high-performance cement materials suitable for marine environments has become an urgent issue.

[0003] In harsh environments such as marine tidal zones, the durability of concrete structures is a key consideration in engineering design and material selection. Ordinary Portland cement (OPC), as the most widely used type of cement, is widely adopted due to its high cost-effectiveness and good availability. However, it has significant shortcomings in its application in marine tidal zones, especially in terms of durability. Ordinary Portland cement is constantly corroded by seawater, especially the penetration of chloride ions, which can cause steel corrosion, thereby reducing the strength and durability of the structure. In addition, the large amount of heat released during the hydration process may cause the internal temperature of the concrete to rise, resulting in temperature stress, which in turn causes cracks, making it unfavorable for use in marine environments.

[0004] Although sulphoaluminate cement (SAC) is favored for its rapid hardening and high early strength, its application in marine tidal zones also faces challenges. In the low alkalinity environment of marine tidal zones, ettringite (AFt), the primary hydration product in SAC, is less stable and prone to decomposition, leading to a decrease in strength later in life, a phenomenon known as strength shrinkage. Furthermore, the difficulty in controlling the setting time of SAC can cause inconvenience during construction, a significant issue for marine engineering projects, which require precise control of construction time.

[0005] In view of these challenges, the development of new cement concrete materials is crucial to improve the durability and performance of concrete structures in marine tidal zones. Summary of the Invention

[0006] In order to overcome the defects of the existing technology, a high-strength and high-seawater corrosion-resistant concrete and a preparation method thereof are provided to solve the problems of poor durability and strength reduction of ordinary Portland cement and sulphoaluminate cement in the application of marine tidal areas.

[0007] To achieve the above object, a high-strength and high-seawater corrosion-resistant concrete is provided, comprising 400 parts by mass of a cementitious material, 1180-1200 parts by mass of a coarse aggregate, 610-640 parts by mass of a fine aggregate, 1.1-1.5 parts by mass of a water-reducing agent, and 175-185 parts by mass of water;

[0008] The cementitious material comprises 310-325 parts by mass of ferroaluminate cement and 75-90 parts by mass of fly ash, or 275-285 parts by mass of ferroaluminate cement and 115-125 parts by mass of mineral powder, or 360-380 parts by mass of ferroaluminate cement and 20-40 parts by mass of silica fume.

[0009] Furthermore, the coarse aggregate is crushed stone, the crushed stone is continuously graded from 5 to 20 mm, and the crushing value of the crushed stone is from 5 to 18%.

[0010] Furthermore, the fineness of the fly ash is 9%, and the apparent density of the fly ash is 2.38 g / cm 3 .

[0011] Furthermore, the density of the mineral powder is 3.1 g / cm 3 The specific surface area of ​​the mineral powder is 429 kg / m 3 .

[0012] Furthermore, the SiO2 content in the silica ash is higher than 95%, and the specific surface area of ​​the silica ash is 18m 2 / g.

[0013] Furthermore, the fine aggregate is natural river sand, and the fineness modulus of the fine aggregate is 2.85.

[0014] Furthermore, the water reducer is a polycarboxylic acid high performance water reducer.

[0015] The present invention provides a method for preparing high-strength and high-seawater corrosion-resistant concrete, comprising the following steps:

[0016] Pour the cementitious material, the coarse aggregate and the fine aggregate into a concrete mixer and dry mix to obtain a dry mix;

[0017] Water and a high-performance water-reducing agent are added to the dry mix and mixed to obtain high-strength and high-seawater corrosion-resistant concrete.

[0018] The beneficial effects of the present invention lie in that the high-strength, highly seawater-resistant concrete employs ferroaluminate cement (FAC) as the primary cementing material. This cement exhibits significant superiority in resisting harmful ion corrosion in seawater due to its higher hydration heat release, faster hydration rate, and ability to form a low-porosity, dense cement stone structure. After seawater wet-dry cycles, the FAC concrete contains a large amount of needle-shaped ettringite, CSH gel, and fluffy AH3 and FH. The large amount of ettringite fills the pores of the FAC concrete. Simultaneously, the ettringite skeleton is covered with a large amount of AH3 and FH3 gel, further filling the pores and increasing the gel pores in the FAC concrete. This reduces medium and large capillary pores, resulting in a denser microporous structure and beneficially improving resistance to chloride ion corrosion.

[0019] In addition, after the seawater dry-wet cycle, the expansive erosion phenomenon caused by the coexistence of gypsum crystals and ettringite crystals that occurs in OPC concrete will not occur in FAC concrete. This is due to the buffering effect of the FH3 gel in FAC, which regulates the expansion amount and speed of the cement stone, improves its density and reduces the damage caused by the later expansion.

[0020] The high-strength and high-seawater corrosion-resistant concrete formula of the present invention, in addition to FAC as the main cementitious material, also specifically adds fly ash, mineral powder and silica fume, which can not only reduce the use cost, but also further improve the concrete's resistance to chloride ion corrosion.

[0021] After the seawater dry-wet cycle, the high-strength and high-seawater corrosion-resistant concrete of the present invention mixed with fly ash contains spherical fly ash particles, which can be used as microscopic filling materials to improve the density of the concrete.

[0022] The addition of fly ash and mineral powder to the high-strength, highly seawater-resistant concrete of the present invention generates rod-shaped Friedel's salts, which help reduce chloride ion permeability and improve the concrete's corrosion resistance. While the addition of fly ash and mineral powder reduces the initial hydration activity of FAC concrete, resulting in a relatively high porosity, these admixtures promote the formation of more CSH gels over time, improving the concrete's microstructure and enhancing the durability of FAC concrete under seawater dry-wet cycling conditions. Furthermore, the increase in medium-sized capillary pores, which have a minimal impact on FAC concrete performance, mitigates the negative impact of increased total porosity on FAC concrete performance.

[0023] Silica fume is a highly active admixture that generates additional calcium silicate hydrate (CSH) gel through a Poisson reaction. This gel helps fill micropores in concrete, thereby improving its density and mechanical properties. Under seawater dry-wet cycling conditions, the high-strength, seawater-corrosion-resistant concrete of the present invention, incorporating silica fume, exhibits a superior pore structure, with a reduced total pore volume and pores primarily concentrated in the mesopore range, significantly enhancing the concrete's density and mechanical properties.

[0024] The pore structure of the high-strength and high-seawater corrosion-resistant concrete of the present invention added with silica fume is denser, while the total pore volume of the high-strength and high-seawater corrosion-resistant concrete of the present invention added with fly ash and mineral powder (GGBS) is increased, and the activity of fly ash and mineral powder in hydration reaction is not as good as that of silica fume, which makes the durability and mechanical properties of the high-strength and high-seawater corrosion-resistant concrete of the present invention added with silica fume more outstanding than those of the high-strength and high-seawater corrosion-resistant concrete of the present invention added with fly ash and GGBS. DETAILED DESCRIPTION

[0025] The present invention will be further described in detail below with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention.

[0026] It should be noted that, in the absence of conflict, the embodiments and features of the embodiments in this application can be combined with each other. The present application will be described in detail below with reference to the embodiments.

[0027] The invention provides a high-strength and high-seawater corrosion-resistant concrete, comprising 400 parts by mass of a cementitious material, 1180-1200 parts by mass of a coarse aggregate, 610-640 parts by mass of a fine aggregate, 1.1-1.5 parts by mass of a water reducer and 175-185 parts by mass of water.

[0028] In some embodiments, the cementitious material includes 310-325 parts by mass of ferroaluminate cement and 75-90 parts by mass of fly ash.

[0029] In this embodiment, the fineness of fly ash is 9%, and the apparent density of fly ash is 2.38 g / cm 3 .

[0030] In some embodiments, the cementitious material includes 275-285 parts by mass of ferroaluminate cement and 115-125 parts by mass of mineral powder.

[0031] In this embodiment, the density of the mineral powder is 3.1 g / cm 3 The specific surface area of ​​the mineral powder is 429kg / m 3 .

[0032] In some embodiments, the cementitious material includes 360-380 parts by mass of ferroaluminate cement and 20-40 parts by mass of silica fume.

[0033] In this embodiment, the SiO2 content in the silica fume is higher than 95%, and the specific surface area of ​​the silica fume is 18m 2 / g.

[0034] In this embodiment, the coarse aggregate is crushed stone, the crushed stone is continuously graded from 5 to 20 mm, and the crushing value of the crushed stone is from 5 to 18%.

[0035] In this embodiment, the fine aggregate is natural river sand, and the fineness modulus of the fine aggregate is 2.85.

[0036] In this embodiment, the water reducer is a polycarboxylic acid high performance water reducer.

[0037] The present invention provides a method for preparing high-strength and high-seawater corrosion-resistant concrete, comprising the following steps:

[0038] S1. Pour the cementitious material, coarse aggregate and fine aggregate into a concrete mixer and dry mix to obtain a dry mix;

[0039] S2. Add water and a high-performance water-reducing agent to the dry mix and mix to obtain high-strength and high-seawater corrosion-resistant concrete.

[0040] When preparing high-strength and high-seawater corrosion-resistant concrete, first accurately weigh various raw materials according to the mix ratio, pour the cementitious material, coarse aggregate and fine aggregate into a concrete mixer and dry mix for 30 to 60 seconds, then slowly add water and high-performance water reducer, continue mixing for 70 to 110 seconds, and cure for 28 days under standard curing conditions to obtain high-strength and high-seawater corrosion-resistant concrete based on ferroaluminate cement and mineral admixtures.

[0041] The high-strength, highly seawater-resistant concrete of the present invention uses ferroaluminate cement (FAC) as its primary cementing material. This cement exhibits significant superiority in resisting harmful ion corrosion in seawater due to its higher hydration heat release, faster hydration rate, and ability to form a low-porosity, dense cement stone structure. After seawater wet-dry cycles, the FAC concrete contains a large amount of needle-shaped ettringite, CSH gel, and fluffy AH3 and FH. The large amount of ettringite fills the pores of the FAC concrete. Simultaneously, the ettringite skeleton is covered with a large amount of AH3 and FH3 gel, further filling the pores and increasing the gel pores in the FAC concrete. This reduces medium and large capillary pores, resulting in a denser microporous structure and beneficially improving resistance to chloride ion corrosion.

[0042] In addition, after the seawater dry-wet cycle, the expansive erosion phenomenon caused by the coexistence of gypsum crystals and ettringite crystals that occurs in OPC concrete will not occur in FAC concrete. This is due to the buffering effect of the FH3 gel in FAC, which regulates the expansion amount and speed of the cement stone, improves its density and reduces the damage caused by the later expansion.

[0043] The high-strength and high-seawater corrosion-resistant concrete formula of the present invention, in addition to FAC as the main cementitious material, also specifically adds fly ash, mineral powder and silica fume, which can not only reduce the use cost, but also further improve the concrete's resistance to chloride ion corrosion.

[0044] After the seawater dry-wet cycle, the high-strength and high-seawater corrosion-resistant concrete of the present invention mixed with fly ash contains spherical fly ash particles, which can be used as microscopic filling materials to improve the density of the concrete.

[0045] The addition of fly ash and mineral powder to the high-strength, highly seawater-resistant concrete of the present invention generates rod-shaped Friedel's salts, which help reduce chloride ion permeability and improve the concrete's corrosion resistance. While the addition of fly ash and mineral powder reduces the initial hydration activity of FAC concrete, resulting in a relatively high porosity, these admixtures promote the formation of more CSH gels over time, improving the concrete's microstructure and enhancing the durability of FAC concrete under seawater dry-wet cycling conditions. Furthermore, the increase in medium-sized capillary pores, which have a minimal impact on FAC concrete performance, mitigates the negative impact of increased total porosity on FAC concrete performance.

[0046] Silica fume is a highly active admixture that generates additional calcium silicate hydrate (CSH) gel through a Poisson reaction. This gel helps fill micropores in concrete, thereby improving its density and mechanical properties. Under seawater dry-wet cycling conditions, the high-strength, seawater-corrosion-resistant concrete of the present invention, incorporating silica fume, exhibits a superior pore structure, with a reduced total pore volume and pores primarily concentrated in the mesopore range, significantly enhancing the concrete's density and mechanical properties.

[0047] The pore structure of the high-strength and high-seawater corrosion-resistant concrete of the present invention added with silica fume is denser, while the total pore volume of the high-strength and high-seawater corrosion-resistant concrete of the present invention added with fly ash and mineral powder (GGBS) is increased, and the activity of fly ash and mineral powder in hydration reaction is not as good as that of silica fume, which makes the durability and mechanical properties of the high-strength and high-seawater corrosion-resistant concrete of the present invention added with silica fume more outstanding than those of the high-strength and high-seawater corrosion-resistant concrete of the present invention added with fly ash and GGBS.

[0048] The high-strength and high-seawater corrosion-resistant concrete of the present invention adopts FAC as the main cementitious material, and utilizes the characteristics of low porosity and dense cement stone structure of the cement, which is conducive to improving the seawater corrosion resistance of the concrete.

[0049] The high-strength and high-seawater corrosion-resistant concrete of the present invention does not exhibit the expansive erosion phenomenon commonly seen in OPC concrete caused by the coexistence of gypsum crystals and ettringite crystals, because the FH3 gel acts as a buffer.

[0050] By optimizing the mix ratio of mineral admixtures and improving the microstructure of concrete, the durability of the high-strength and high-seawater corrosion-resistant concrete of the present invention under seawater dry-wet cycle conditions is effectively improved.

[0051] The addition of fly ash and mineral powder can improve the density of the high-strength and high-seawater corrosion-resistant concrete of the present invention, generate Friedel's salt, reduce chloride ion permeability, and improve corrosion resistance.

[0052] The silica fume in the high-strength and high-seawater corrosion-resistant concrete of the present invention generates additional CSH gel through Poisson reaction, which helps to fill micropores and improve the density and mechanical properties of the high-strength and high-seawater corrosion-resistant concrete of the present invention.

[0053] The high-strength and high-seawater corrosion-resistant concrete of the present invention has a compressive strength range of 50 to 74 MPa after 28 days of standard curing, and a compressive strength of 67 to 78 MPa after 140 days of dry-wet cycling. After the dry-wet cycling of seawater, the compressive strength is enhanced, meeting the strength requirements of structures in marine tidal zones.

[0054] The results of the high-strength and high-seawater corrosion-resistant concrete of the present invention after 140 days of seawater dry-wet cycles are as follows:

[0055] At 0 to 5 cm from the concrete surface, the free chloride ion content of concrete is 0.42% when it does not contain mineral admixtures, which drops to 0.29% when it is added with fly ash, 0.27% when it is added with mineral powder, and 0.24% when it is added with silica fume.

[0056] The total chloride ion content of concrete is 0.47% when it does not contain fly ash, which drops to 0.31% when it is added with fly ash, 0.29% when it is added with mineral powder, and 0.27% when it is added with silica fume.

[0057] At 0 to 5 cm from the concrete surface, the chloride ion binding capacity of concrete is 0.11% when it does not contain mineral admixtures, which increases to 0.15% when fly ash is added, 0.16% when mineral powder is added, and 0.16% when silica fume is added.

[0058] The chloride ion diffusion coefficient of concrete without mineral admixture is 1.31×10 -6 mm 2 / s, and when fly ash is added, it is reduced to 1.12×10 -6 mm 2 / s, and when adding mineral powder, it is reduced to 1.09×10 -6 mm 2 / s, and it is reduced to 1.06×10 -6 mm 2 / s, adding appropriate amount of mineral admixtures can effectively reduce the chloride ion diffusion coefficient.

[0059] The addition of fly ash and mineral powder promotes the formation of more CSH gel, improves the concrete's microstructure, and enhances its durability under seawater dry-wet cycles. The addition of silica fume reduces the total pore volume of concrete and concentrates pores in the mesopore range, improving its density and mechanical properties.

[0060] The high-strength and high-seawater corrosion-resistant concrete and its preparation method of the present invention are further illustrated below by using specific examples 1 to 3 and comparative example 1.

[0061] Example 1

[0062] Table 1 shows the mix ratio of the high-strength and high-seawater corrosion-resistant concrete in Example 1.

[0063] Table 1. Mix ratio of concrete in Example 1

[0064]

[0065] Among them: the coarse aggregate is ordinary crushed stone, with continuous grading of 5 to 20 mm and a crushing value index of 5% to 18%.

[0066] The fly ash is Class I fly ash.

[0067] The fine aggregate is natural river sand, and the fineness modulus of the fine aggregate is 2.85.

[0068] The water reducer is a polycarboxylic acid high-performance water reducer with a water reduction rate of ≥25% produced by Beijing Muhu Admixture Co., Ltd.

[0069] The cement is produced by Guangxi Yunyan Special Cement Building Materials Co., Ltd. with a density of 2.94-2.99 g / cm 3 , specific surface area 400m 2 / kg of 42.5 ferroaluminate cement.

[0070] Raw materials were selected according to the raw material ratios shown in Table 1. Cement, fly ash, water, coarse aggregate, and fine aggregate were poured into a concrete mixer and stirred for 30 seconds. Water and a water reducer were then added and stirring continued for 70 to 110 seconds to produce high-strength, high-seawater corrosion-resistant concrete. The durability performance technical indicators of the high-strength, high-seawater corrosion-resistant concrete of this example are listed in Tables 5, 6, 7, 8, and 9.

[0071] Example 2

[0072] Table 2 shows the mix ratio of high strength and high seawater corrosion resistance concrete in Example 2

[0073] Table 2, the mix ratio in Example 2

[0074]

[0075] Among them: the coarse aggregate is ordinary crushed stone, with continuous grading of 5 to 20 mm and a crushing value index of 5% to 18%.

[0076] The slag powder is S95 blast furnace slag powder.

[0077] The fine aggregate is natural river sand, and the fineness modulus of the fine aggregate is 2.85.

[0078] The water reducer is a polycarboxylic acid high-performance water reducer with a water reduction rate of ≥25% produced by Beijing Muhu Admixture Co., Ltd.

[0079] The cement is produced by Guangxi Yunyan Special Cement Building Materials Co., Ltd. with a density of 2.94-2.99 g / cm 3 , specific surface area 400m 2 / kg of 42.5 ferroaluminate cement.

[0080] Raw materials were selected according to the raw material ratios in Table 2. Cement, mineral powder, water, coarse aggregate, and fine aggregate were poured into a concrete mixer and stirred for 30 seconds. Water and a water reducer were then added and stirring continued for 70 to 110 seconds to produce high-strength, high-seawater corrosion-resistant concrete. The durability performance technical indicators of the high-strength, high-seawater corrosion-resistant concrete of this example are listed in Tables 5, 6, 7, 8, and 9.

[0081] Example 3

[0082] Table 3 shows the mix ratio of high strength and high seawater corrosion resistance concrete in Example 3

[0083] Table 3, the mix ratio in Example 3

[0084]

[0085] Among them: the coarse aggregate is ordinary crushed stone, with continuous grading of 5 to 20 mm and a crushing value index of 5% to 18%.

[0086] The SiO2 content of silica fume is higher than 95%.

[0087] The fine aggregate is natural river sand, and the fineness modulus of the fine aggregate is 2.85.

[0088] The water reducer is a polycarboxylic acid high-performance water reducer with a water reduction rate of ≥25% produced by Beijing Muhu Admixture Co., Ltd.

[0089] The cement is produced by Guangxi Yunyan Special Cement Building Materials Co., Ltd. with a density of 2.94-2.99 g / cm 3 , specific surface area 400m 2 / kg of 42.5 ferroaluminate cement.

[0090] Raw materials were selected according to the raw material ratios shown in Table 2. Cement, silica fume, water, coarse aggregate, and fine aggregate were poured into a concrete mixer and stirred for 30 seconds. Water and a water reducer were then added and stirring continued for 70 to 110 seconds to produce high-strength, high-seawater corrosion-resistant concrete. The durability performance technical indicators of the high-strength, high-seawater corrosion-resistant concrete of this example are listed in Tables 5, 6, 7, 8, and 9.

[0091] Comparative Example 1

[0092] Table 4 shows the mix ratio of concrete in Comparative Example 1

[0093] Table 4, the mix ratio in comparative example 1

[0094]

[0095] Among them: the coarse aggregate is ordinary crushed stone, with continuous grading of 5 to 20 mm and a crushing value index of 5% to 18%.

[0096] The fine aggregate is natural river sand, and the fineness modulus of the fine aggregate is 2.85.

[0097] The water reducer is a polycarboxylic acid high-performance water reducer with a water reduction rate of ≥25% produced by Beijing Muhu Admixture Co., Ltd.

[0098] The cement is produced by Guangxi Yunyan Special Cement Building Materials Co., Ltd. with a density of 2.94-2.99 g / cm3 and a specific surface area of ​​400 m 2 / kg of 42.5 ferroaluminate cement.

[0099] Raw materials were selected according to the raw material ratios listed in Table 4. Cement, water, coarse aggregate, and fine aggregate were poured into a concrete mixer and stirred for 30 seconds. Water and a water reducer were then added and stirring continued for 70 to 110 seconds to produce high-strength, high-seawater corrosion-resistant concrete. The durability performance technical indicators of the concrete of Comparative Example 1 are listed in Tables 5, 6, 7, 8, and 9. Comparative Example 1 in the tables represents FAC concrete with the same water-binder ratio and no mineral admixtures.

[0100] Table 5. Free chloride ion content of concrete (%)

[0101]

[0102] Table 6. Total chloride ion content of concrete (%)

[0103]

[0104] Table 7. Concrete chloride ion binding capacity / (%)

[0105]

[0106] Table 8, Concrete chloride ion diffusion coefficient / (10 -6 mm 2 / s)

[0107]

[0108] Table 9. Compressive strength of concrete cubes / MPa

[0109]

[0110] Tables 5 and 6 illustrate that the high-strength and high-seawater corrosion-resistant concrete according to the present invention can effectively reduce the chloride ion content in the concrete under seawater dry-wet cycle conditions, thereby improving its durability and resistance to chloride corrosion.

[0111] Table 7 illustrates that the high-strength and high-seawater corrosion-resistant concrete according to the present invention has excellent chloride ion binding ability and strong resistance to chloride ion penetration under dry-wet cycle conditions.

[0112] Table 8 illustrates that the high-strength and high-seawater corrosion-resistant concrete according to the present invention has a low chloride ion diffusion coefficient, a small structural porosity, and a more compact concrete under dry and wet environmental conditions.

[0113] Table 9 shows that the high-strength and high-seawater corrosion-resistant concrete according to the present invention has a relatively significant improvement in compressive strength after seawater dry-wet cycles under dry and wet environmental conditions, and has good anti-deterioration ability.

[0114] The specific raw materials listed in the present invention, as well as the upper and lower limits and intervals of each raw material, can all achieve the present invention, and embodiments are not listed here one by one. Through the above embodiments, ferroaluminate cement concrete with excellent durability can be produced, which is resistant to chloride ion penetration and other harsh environments.

[0115] The high-strength and high-seawater corrosion-resistant concrete of the present invention significantly improves the durability and resistance to chloride ion penetration of the concrete by optimizing the raw material mix ratio and adding an appropriate amount of mineral admixtures, especially the resistance to chloride ion penetration and other environments, and has broad application prospects.

[0116] In order to further illustrate the compressive strength of the high-strength and high-seawater corrosion-resistant concrete of the present invention, the following comparative examples 2 to 4 are used for comparison with embodiments 1 to 3.

[0117] Comparative Example 2

[0118] The concrete in this comparative example consisted of 528g of ferroaluminate cement, 475g of Grade I fly ash, 317g of Grade S95 mineral powder, 4600g of medium sand with a particle size distribution curve in Zone II, and 844g of water. The total amount of fly ash and mineral powder accounted for 60% of the total amount of cement, fly ash, and mineral powder added. The steps in the preparation method of the marine erosion-resistant low-carbon, low-strength cement-based material were strictly implemented in accordance with the patent. After 28 days of curing under standard conditions, the compressive strength of the material is shown in Table 10.

[0119] Comparative Example 3

[0120] The concrete in this comparative example consisted of 555g of ferroaluminate cement, 666g of Grade I fly ash, 167g of Grade S95 mineral powder, 4600g of medium sand with a particle size distribution curve in Zone II, and 844g of water. The total amount of fly ash and mineral powder accounted for 60.01% of the total amount of cement, fly ash, and mineral powder. The steps in the preparation method of the marine erosion-resistant low-carbon, low-strength cement-based material were strictly implemented in accordance with the patent. After 28 days of curing under standard conditions, the compressive strength is shown in Table 10.

[0121] Comparative Example 4

[0122] The concrete in this comparative example included 534g of ferroaluminate cement, 561g of Grade I fly ash, 240g of Grade S95 mineral powder, 4600g of medium sand with a particle size distribution curve in Zone II, and 844g of water. The total amount of fly ash and mineral powder accounted for 60% of the total amount of cement, fly ash, and mineral powder added. The steps in the preparation method of the marine erosion-resistant low-carbon, low-strength cement-based material were strictly carried out in accordance with the patent. After 28 days of curing under standard conditions, the compressive strength is shown in Table 10.

[0123] Table 10. Compressive strength of concrete cubes / MPa

[0124]

[0125] The test results show that when ferroaluminate cement concrete is used in the comparative patent, its cubic compressive strength is still low and cannot be used in structures.

[0126] The above description is merely a preferred embodiment of the present application and an illustration of the technical principles employed. Those skilled in the art should understand that the scope of the invention herein is not limited to the technical solutions formed by the specific combination of the above-mentioned technical features, but also encompasses other technical solutions formed by any combination of the above-mentioned technical features or their equivalents without departing from the inventive concept. For example, a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features having similar functions disclosed in this application.

Claims

1. A high-strength and high-seawater corrosion-resistant concrete, characterized in that: The invention comprises 400 parts by weight of cementitious material, 1180-1200 parts by weight of coarse aggregate, 610-640 parts by weight of fine aggregate, 1.1-1.5 parts by weight of water reducing agent and 175-185 parts by weight of water; The cementitious material comprises 310-325 parts by mass of ferroaluminate cement and 75-90 parts by mass of fly ash, or 275-285 parts by mass of ferroaluminate cement and 115-125 parts by mass of mineral powder, or 360-380 parts by mass of ferroaluminate cement and 20-40 parts by mass of silica fume.

2. The high-strength and high-seawater corrosion-resistant concrete according to claim 1, characterized in that: The coarse aggregate is crushed stone, the crushed stone is 5-20 mm continuously graded, and the crushing value of the crushed stone is 5-18%.

3. The high-strength and high-seawater corrosion-resistant concrete according to claim 1 is characterized in that: The fineness of the fly ash is 9%, and the apparent density of the fly ash is 2.38 g / cm 3 .

4. The high-strength and high-seawater corrosion-resistant concrete according to claim 1, characterized in that: The density of the mineral powder is 3.1 g / cm 3 The specific surface area of ​​the mineral powder is 429 kg / m 3 .

5. The high-strength and high-seawater corrosion-resistant concrete according to claim 1, characterized in that: The SiO2 content of the silica ash is higher than 95%, and the specific surface area of ​​the silica ash is 18m 2 / g.

6. The high-strength and high-seawater corrosion-resistant concrete according to claim 1, characterized in that: The fine aggregate is natural river sand, and the fineness modulus of the fine aggregate is 2.

85.

7. The high-strength and high-seawater corrosion-resistant concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid high performance water reducing agent.

8. A method for preparing high-strength and high seawater corrosion-resistant concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: Pour the cementitious material, the coarse aggregate and the fine aggregate into a concrete mixer and dry mix to obtain a dry mix; Water and a high-performance water reducing agent are added to the dry mix and mixed to obtain high-strength and high-seawater corrosion-resistant concrete.